Pilgrimage and holy space in late antique Egypt - Frankfurter, David, 1961- (Religions in the Graeco-Roman World, 1998)
This volume deals with the origins and rise of Christian pilgrimage cults in late antique Egypt. Part One covers the major theoretical issues in the study of Coptic pilgrimage, such as sacred landscape and shrines' catchment areas, while Part Two examines native Egyptian and Egyptian Jewish pilgrimage practices. Part Three investigates six major shrines, from Philae's diverse non-Christian devotees to the great pilgrim center of Abu Mina and a Thecla shrine on its route. Part Four looks at such diverse pilgrims' rites as oracles, chant, and stational liturgy, while Part Five brings in Athanasius's and an anonymous hagiographer's perspectives on pilgrimage in Egypt. The volume includes illustrations of the Abu Mina site, pilgrims' ampules from the Thecla shrine, as well as several maps.